A apropriação do acervo do PNBE em oficinas literárias - (:unkn) unknown (Universidade Federal de Goiás, 2016)
The goal of this research is to track the movement and the effective use of the National Program of School Library collection (PNBE) by students who are part of the literacy course of an educational institution in the state of Goiás, from the moment that literary works enter the school environment. Make reading democratization an affordable reality to everyone has been a challenging task assumed by the federal government. Based on discussions that curtail public policy for the distribution of children's literature books and research and reference materials to basic education schools in the country, it is sought to examine whether literary works belonging to the program are appropriate for students the first, second and third year of elementary education of the school. Several actions were implemented over nearly two decades, and the execution of PNBE involves different stakeholders to the final stage of the process, which is in the ownership of cultural property by the student in the educational context. The relevance of this topic is supported by the fact that research has dealt with the circulation and distribution of the PNBE collection; however, there are few studies that purport to understand the use of these literary books distributed by official agencies (PAIVA, 2012). Believing that reading can expand the reference world of the student, in addition to working concurrently with different languages, such as writing, sound, drama, film, body and other (PEROTTI, 1990), there is the concern to distinguish the modalities of reading and modes of understanding of the text (BAJARD, 2014b). The methodology used in this study, of a qualitative approach, is ethnographic and seeks to identify situations that go unnoticed in the school routine (BORTONI-RICARDO, 2008). Based on document analysis and intervention, achieved through literary workshops, data collection instruments include: the observation of students in the use of the works of PNBE; questionnaire and interview with the rulers of the school literacy cycle of the school investigated and the library employees; and workshops on reading, writing and producing material, developed with the aim of expanding the use of the program's collection in that environment. With this study, it is concluded that the PNBE books are being appropriated by those students, albeit in a modest way. It is noteworthy that through the intervention is not sought the immediate change of the actions instituted at the school, but contributes to reflection on practices that can transform the habit of reading the same as the construction of the reader practice is rooted in school time (MEIRELES, 1979).
Ownership of PNBE the collection in literary workshops
Keywords: PNBE; Leitura; Livros literários; Reading; Literary books; CIENCIAS HUMANAS::EDUCACAO